2016
DOI: 10.1007/s00270-016-1366-6
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Biopsy and Radiofrequency Ablation of Osteoid Osteoma with Excess Reactive New Bone Formation and Cortical Thickening Using a Battery-Powered Drill for Access: A Technical Note

Abstract: The use of battery-powered drill facilitates access to the osteoid osteoma nidus in cases where excess reactive new bone formation is present. Biopsy needle can be used for channel creation during the access offering at the same time the possibility to extract bone samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Procedure time was significantly reduced with the use of mechanical drills [13,14]. Schnapauff et al [14] reported 23 cases where a battery-charged drill (OBM, Arrow OnControl, Teleflex, Shavano Park, TX, USA) was used and compared the procedure time, number of scans and radiation exposure with those obtained from historical manual bone biopsy systems or conventional orthopaedic drills.…”
Section: Discussionmentioning
confidence: 99%
“…Procedure time was significantly reduced with the use of mechanical drills [13,14]. Schnapauff et al [14] reported 23 cases where a battery-charged drill (OBM, Arrow OnControl, Teleflex, Shavano Park, TX, USA) was used and compared the procedure time, number of scans and radiation exposure with those obtained from historical manual bone biopsy systems or conventional orthopaedic drills.…”
Section: Discussionmentioning
confidence: 99%
“…The entry point view, in which skin entry point and target were superimposed, was used to locate the skin entry point and place the drill (OnControl Bone Lesion Biopsy System, Teleflex Medical, Morrisville, USA) in the angulation of the planned path [13]. Rotating the C-arm to progress view, perpendicular to the needle path, allowed visualization of the drill-tip in relation to the nidus.…”
Section: Methodsmentioning
confidence: 99%
“…The choice of appropriate bone biopsy system depends mainly upon the presence of an intact cortical bone; in such a case, a trocar should be used for the coaxial approach which will also allow the operator to get multiple samples with one puncture ( Figure 1 and Figure 2 ) [ 18 ]. Cases of a cortical bone with increased thickness and excessive periosteal reaction drilling rather than hammering could be technically easier [ 19 , 20 , 21 ].…”
Section: Techniquesmentioning
confidence: 99%